2005
DOI: 10.1203/01.pdr.0000150804.18038.79
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Ketogenic Diet on the Activity Level of Wistar Rats

Abstract: Children, adolescents, and adults with epilepsy often also show symptoms associated with attention-deficit/hyperactivity disorder (ADHD). The ketogenic diet, which is administered to children with epilepsy refractory to drug therapy, seems to improve behavior in individuals with symptoms of ADHD. The basis for this improvement is unknown, although it seems to be unrelated to seizure control. The present research was designed to investigate the effect of two ketogenic diets on the behavior of normal adult male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…This raises an important question regarding the possible effects of a high-fat diet in wild-type littermates and whether this dietary modification might have influenced the behavior of the mutants. Burnham and co-workers conducted a series of studies on the effects of different KD formulas on locomotor activity in different strains of rats [15,16]. Diets with fat:carbohydrate plus protein ratios of 6.3:1, 4:1 (present study also), and 3:1 resulted in a reversible decrease in exploratory activity unrelated to anxiety, sedation, or ataxia.…”
Section: Technical Considerationsmentioning
confidence: 66%
“…This raises an important question regarding the possible effects of a high-fat diet in wild-type littermates and whether this dietary modification might have influenced the behavior of the mutants. Burnham and co-workers conducted a series of studies on the effects of different KD formulas on locomotor activity in different strains of rats [15,16]. Diets with fat:carbohydrate plus protein ratios of 6.3:1, 4:1 (present study also), and 3:1 resulted in a reversible decrease in exploratory activity unrelated to anxiety, sedation, or ataxia.…”
Section: Technical Considerationsmentioning
confidence: 66%
“…In addition, the swimming speed results obtained from the MWM test revealed that motor ability was slightly increased by KD in kindled group but not in non-kindled group. Other researchers have observed a reduction (Murphy et al, 2005) or a transient increase (Zhao et al, 2004;Ziegler et al, 2005) in locomotor activity in nonkindled animals. It seemed that the animal age, maintenance time of KD, seizure model lead to different results.…”
Section: Discussionmentioning
confidence: 89%
“…Rats on the KD demonstrate less depressive behavior, and rats in which formation of neuroactive steroids was blocked show more depressive behavior [80]. The KD also decreases activity levels in an animal model of attention deficit/hyperactivity disorder [81]. Notably, both of these processes may involve actions of neurosteroids.…”
Section: Discussionmentioning
confidence: 99%